Antenatal paternal adjustment and paternal attitudes after infertility treatment - Pinto, TM (2018)
Study question: Do mode of conception [ART versus Natural (NC)] and depression have an interactive effect on antenatal paternal adjustment and paternal attitudes? Summary answer: Depression increased the negative effect of ART on antenatal paternal adjustment and paternal attitudes, specifically on antenatal marital relationship satisfaction. What is known already: Research on antenatal paternal adjustment and paternal attitudes after ART is scarce and has produced inconsistent results. Study design, size, duration: This cross-sectional study assessed 197 primiparous men (71 ART and 126 NC) during their partner's second trimester of gestation. Participants/materials, setting, methods: Participants were derived from three larger longitudinal studies recruited at public Health Services in Northern Portugal. All men, for who this was their first child and had filled in a socio-demographic questionnaire, measures of depression and anxiety, and antenatal paternal adjustment and paternal attitudes were selected. Main results and the role of chance: An interaction effect of mode of conception and depression was found on antenatal paternal adjustment and paternal attitudes. ART men showing high depressive symptomatology had lower antenatal marital relationship satisfaction than ART men showing low depressive symptomatology and NC men showing high or low depressive symptomatology. Limitations, reasons for caution: Due to the cross-sectional design of this study and the small sample size in the depression groups, the findings should be interpreted with caution. Wider implications of the findings: Specialized psychological support should be available for ART men screened with high depressive symptomatology as part of routine prenatal care appointments.